Evaluación de la eficiencia energética en calderas operativas de Campo Rubiales (2021)
In the present degree work, the energy evaluation of the Rubiales field boilers was carried out, with the aim of estimating the potential of the current fuel to be able to define a new fuel mixture with which to reduce the emission of pollutants to the atmosphere. To achieve the final objective of the work, it was necessary to characterize the field boilers under current operating conditions, this together with the characterization of the hydrocarbons available for combustion (produced by the Rubiales field); Because in this way it would be possible to identify the faults that are occurring in the steam generating equipment, and thus be able to recommend a fuel mixture between crude oil and residual distillate, the proportion of which was established through the application of material and energy balances, together with simulations of the thermodynamic properties of these fuels.